Peningkatan Produktifitas Usaha Peternakan Kambing melalui Perbaikan Manajemen Usaha - Siamsa, Simon; Wati, Caecilia Henny Setya; Rizal, Abdul; Awotkay, Apolinaris Sapuk; Djanggo, Romualdus Turu Putra Maro; Suwarjono, Suwarjono (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The majority of goat livestock businesses are managed by the transmigration community as a side business. The impact that occurs is that the management of the business that is being carried out is not optimal both institutionally, marketing and housing. This of course will affect production and business productivity. Goat livestock business managed by breeders is still small-scale and imbreading occurs. On the other hand, the marketing process carried out only relied on personal communication within the scope of the village itself. The approach to the activities carried out is direct counseling to breeders as well as providing goat seeds and cage rehabilitation.